A sensitive and selective fluorescent sensor for the determination of mercury(II) based on a novel triazine-thione derivative - Aksuner, Nur; Basaran, Beyza; Henden, Emur; Yilmaz, Ibrahim; Cukurovali, Alaaddin (Elsevier Sci Ltd, 2011)
A sensor membrane based on the fluorescence enhancement of a novel triazine-thione derivative, 4-ethyl-5-hydroxy-5,6-di-pyridin-2-yl-4,5-dihydro-2H-[1,2,4]triazine-3-thione, was capable of determining mercury(II) with high selectivity over the range 5.0 x 10(-10) and 5.0 x 10(-5) mol L(-1) with a limit of detection of 1.8 x 10(-10) mol L(-1) (0.036 mu g L(-1)). The sensor can be regenerated using 5% thiourea in 1.0 mol L(-1) HCl solution. The sensor also displayed unique selectivity toward mercury(II) ion with respect to other common metal cations and was applied to the determination of mercury(II) in tap water and human hair samples. The accuracy of the results were comparable to those obtained by cold vapour atomic fluorescence spectrometry. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Optical sensor; PVC matrix; Fluorescence spectroscopy; Fluorescence enhancement; Mercury(II); Triazine-thione